2018
DOI: 10.1177/0748730418764540
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Strengthens Molecular Link between Circadian Polymorphisms and Major Mood Disorders

Abstract: Anxiety and other mood disorders, such as major depressive disorder (MDD) and seasonal affective disorder (SAD), affect nearly one-fifth of the global population and disproportionately affect young adults. Individuals affected by mood disorders are frequently plagued by sleep and circadian problems, and recent genetic studies provide ample support for the association of circadian and sleep syndromes with depression and anxiety. Mathematical modeling has been crucial in understanding some of the essential featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 99 publications
2
37
0
2
Order By: Relevance
“…This is perhaps surprising given the literature on circadian rhythmicity and mood disorders. Core circadian clock genes have been associated with both BD and depression, with altered circadian biology suggested to be a vulnerability marker for mood disorders [ [70] , [71] , [72] , [73] , [74] ]. It has been suggested that the treatment of disrupted circadian rhythmicity could be used in combination with current pharmaceutical therapies to develop more effective treatments for mood disorders [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps surprising given the literature on circadian rhythmicity and mood disorders. Core circadian clock genes have been associated with both BD and depression, with altered circadian biology suggested to be a vulnerability marker for mood disorders [ [70] , [71] , [72] , [73] , [74] ]. It has been suggested that the treatment of disrupted circadian rhythmicity could be used in combination with current pharmaceutical therapies to develop more effective treatments for mood disorders [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two specific polymorphisms examined in this study alter coding regions containing phosphorylation sites. Reduced phosphorylation of PER3 may be associated with a lengthening of period and a delay in the circadian phase, both of which are typically associated with an evening phenotype [14462524]. This delay in circadian phase exacerbates the social jetlag (or misalignment of internal rhythms with daily sleep patterns) [423043], and likely enhances the offset in the physiological peak of evening-types.…”
Section: Discussionmentioning
confidence: 99%
“…One candidate mechanism is the PER3 gene, a highly rhythmic, circadian-related gene with expression in both the central nervous system and peripheral tissues (Archer et al, 2018). In humans, variants of the PER3 gene are associated with chronotype, sleep homeostasis, and mental disorders (Archer et al, 2003;Johansson et al, 2003;Akashi et al, 2010;McClung, 2013;Hida et al, 2014;Zhang et al, 2016;Liberman et al, 2017Liberman et al, , 2018Nguyen et al, 2019). A well-studied PER3 polymorphism in exon 18, rs57875989, encodes a variable number tandem repeat region (VNTR) containing a motif of 54 base pairs or 18 amino acids.…”
Section: Introductionmentioning
confidence: 99%